ANALYSIS AND MAPPING OF HEAT SOURCES IN THE ARIOCA PRUANÃ EXTRACTIVE RESERVE, IN OEIRAS DO PARÁ-PA. (REMUNOM, 2026)
The traditional practice of using fire is common among rural populations and has become a growing pressure factor on the integrity of these territories, particularly in the Amazonian biome. Given this scenario, this research aimed to quantify and analyze the spatial and temporal dynamics of hotspots in the Arióca Pruanã Extractive Reserve, located in Oeiras do Pará (PA), covering the period from 2021 to 2024. For the analysis, hotspot data obtained from the NOAA-21, AQUA, TERRA, and S-NPP satellites were used. Geospatial processing and analysis were performed using QGIS 3.16.11 software. The spatial distribution was modeled using the Kernel Density Estimator (KDE), whose radius of influence was defined by the Silverman optimization methodology (1986). The results revealed a high recurrence of the phenomenon, with a total of 1,840 hotspots recorded inside the RESEX and 5,422 in its buffer zone. The year 2023 concentrated the greatest severity of the phenomenon, with a notable peak in the months of October and November, responsible for more than 80% of the annual records. Spatially, the highest concentrations of hotspots were observed in the southern and southeastern portions of the reserve, in transition areas between native vegetation and zones under anthropic intervention. The Arióca Pruanã RESEX faces a critical vulnerability to fires, governed by the complex interaction between climatic factors and land use in the surrounding area. The application of KDE proved to be an effective tool in identifying and delimiting the areas of greatest risk, providing indispensable subsidies for improving the planning of prevention actions and Integrated Fire Management.